Functional Evolution of Experimental Design in Sports Science: From Bibliometric Analysis to a Functional Concept - Khudolii, Oleg; Ivashchenko, Olha; Khudolii, Mykola (Physical Education Theory and Methodology, 2026)
Background. Experimental design is the principal methodological framework for establishing causal relationships in sports science. Traditional classifications describe experimental designs according to structural characteristics, such as the number of factors, randomization procedures, measurement organization, or statistical methods. However, these approaches do not explain how the methodological functions of experimental design evolve from hypothesis testing to mathematical modelling, programming, and model-based decision making. Objectives. To investigate the functional evolution of experimental design in sports science, determine the methodological role of full factorial experiments (2^k), and develop a functional concept of experimental design based on bibliometric and systematic methodological analyses. Material and Methods. The study was conducted in two stages. First, a bibliometric analysis of publications indexed in the Scopus database (2000–2026) was performed to identify the structure of research on experimental designs and to construct an analytical corpus. After duplicate removal, the bibliometric corpus comprised 1653 publications. Second, a systematic methodological analysis of a specialized corpus of 244 publications was carried out to evaluate the realization of the cognitive and constructive potential of experimental designs. Particular attention was paid to studies integrating full factorial experiments with mathematical modelling, regression analysis, and discriminant analysis. Results. The bibliometric analysis demonstrated that contemporary sports science is dominated by subject-oriented terminology, whereas methodological concepts related to experimental design are rarely represented in author keywords or publication titles. The systematic methodological analysis showed that experimental designs with similar structural characteristics perform substantially different methodological functions. A functional concept of experimental design was developed, according to which its methodological significance is determined by the level of realization of its cognitive and constructive potential. Full factorial experiments were identified as the methodological link connecting experimental analysis with mathematical modelling. Three levels of realization of the constructive potential of experimental design were identified: local model-based control, programming of the pedagogical process, and system-level management. Conclusions. The study proposes a functional concept of experimental design that complements traditional structural classifications. The methodological contribution of the study consists in introducing a new principle for classifying experimental designs according to the level of realization of their cognitive and constructive potential. Full factorial experiments occupy a central methodological position in this framework by enabling the transition from hypothesis testing to mathematical modelling, programming, and model-based management of pedagogical and training processes.